(untitled) (Jurnal Pedagogik Olahraga, 2025)
The purpose of this study was to determine the effect of leg curl and leg extension on the results of shooting accuracy and which form of training is better for improving shooting results. This research uses an experimental method. The population in this study were all male futsal extracurricular participants at SMA Negeri 2 Tegal City, totaling 20 people. The sampling technique used in this study was total sampling, so that the number of samples in this study amounted to 20 people. The results of this study are the effect of leg curl training with an increase of 59% and leg extension of 55% on shooting accuracy, and the form of leg curl training is more effective than leg extension training which can be seen from the results of the increase. Therefore, the author suggests that leg curl training be integrated intensively in the training program as the main choice of lower muscle strengthening, while still considering the athlete’s physical condition to prevent injury. Proportional combination with leg extension training is also recommended to obtain more balanced and comprehensive training results. Translated with DeepL.com (free version)